Amygdala Regulation Following fMRI-Neurofeedback without Instructed Strategies - Marxen, Michael; Jacob, Mark J.; Müller, Dirk K.; Posse, Stefan; Ackley, Elena; Hellrung, Lydia; Riedel, Philipp; Bender, Stephan; Epple, Robert; Smolka, Michael N. (Frontiers in Human Neuroscience, 2016)
Within the field of fMRI neurofeedback, most studies provide subjects with instructions or suggest strategies to regulate a particular brain area, while other neuro-/biofeedback approaches often do not. This study is the first to investigate the hypothesis that subjects are able to utilize fMRI neurofeedback to learn to differentially modulate the fMRI signal from the bilateral amygdala congruent with the prescribed regulation direction without an instructed or suggested strategy and apply what they learned even when feedback is no longer available . Thirty-two subjects were included in the analysis. Data were collected at 3 Tesla using BOLD-sensitivity optimized multi-echo EPI. Based on the mean contrast between up- and down-regulation in the amygdala in a post-training scan without feedback following three neurofeedback sessions, subjects were able to regulate their amygdala congruent with the prescribed directions with a moderate effect size of Cohen’s d = 0.43 (95% conf. int. 0.23-0.64). This effect size would be reduced, however, through stricter exclusion criteria for subjects that show alterations in respiration. Regulation capacity was positively correlated with subjective arousal ratings and negatively correlated with agreeableness and susceptibility to anger. A learning effect over the training sessions was only observed with end-of-block feedback but not with continuous feedback (trend). The results confirm the above hypothesis. Further studies are needed to compare effect sizes of regulation capacity for approaches with and without instructed strategies.